Post-stroke malnutrition and associated factors in stroke survivors undergoing rehabilitation - Ying, C.Y. (2021)
Introduction: Stroke is a significant global health burden. Malnutrition is a common health problem after stroke which results in poorer responses in stroke survivors to rehabilitation and interferes with the recovery of stroke survivors. This study aimed to determine the prevalence of post-stroke malnutrition and its associated factors. Methods: In this cross-sectional study, a total of 172 stroke survivors were recruited from the rehabilitation clinic or centre. Post-stroke malnutrition was defined by having a low body mass index (BMI) (BMI <18.5 kg/m2 for <65 years; BMI <22.0 kg/m2 for ≥65 years). Results: Stroke survivors had a median age of 60.0 ± 15.0 years (age range 26 to 82 years). The percentages of underweight, normal, overweight, and obese participants were 4.1%, 43.0%, 35.5%, and 17.4%, respectively. The prevalence of post-stroke malnutrition based on BMI was 13.4%. The final regression model verified that increasing age, high risk of malnutrition, and decreasing carbohydrate intake were the significant predictors of post-stroke malnutrition. Conclusion: Early detection of malnutrition in stroke survivors, especially in those who are at high risk of malnutrition, from the elderly population, and poor dietary intake, should serve as a foundation in developing strategies for preventing post-stroke malnutrition across all populations and demographics.